Chapter Il potenziale corporeo nell'azione didattica - SIBILIO, Maurizio (Studies on Adult Learning and Education, 2022)
The stimulating reflections in the field of the new cognitive sciences have added breath of life to studies on didactics towards an original reinterpretation of educational practices based on the valorization of the body as a founding pedagogical device of educational and training processes. The emergence of an embodied vision of cognition and the recognition of a dynamic dialogicality between the organism and the environment have prompted the construction of new research paths, creating the conditions for the recognition of the learning, communicative, simulative and vicarious potential of corporeity in teaching-learning processes. Teaching, as a science of human interaction, is enriched with verbal, iconic and bodily codes, manifesting teaching postures and corporeity that highlight its nature as a complex adaptive system.